A Note on Public Debt, Tax-Exempt Bonds, and Ponzi Games - Wigger, Berthold (IMF Working Papers; Working Paper ;, 2007)
By issuing tax-exempt bonds, the government can incur debt and never pay back any principal or interest, even if the economy without public debt evolves on a dynamically efficient growth path. The welfare effects of such a Ponzi type borrowing scheme are mixed. The current young will unambiguously benefit.Depending on preferences and the aggregate technology, also a finite number of subsequent generations may benefit. The welfare of all generations thereafter, however, will be lower than in the economy without public debt.